Toward direct MRI of neuro‐electro‐magnetic oscillations in the human brain. Issue 6 (16th January 2019) - Truong, Trong‐Kha; Roberts, Kenneth C.; Woldorff, Marty G.; Song, Allen W.
Abstract : Purpose: Neuroimaging techniques are widely used to investigate the function of the human brain, but none are currently able to accurately localize neuronal activity with both high spatial and temporal specificity. Here, a new in vivo MRI acquisition and analysis technique based on the spin‐lock mechanism is developed to noninvasively image local magnetic field oscillations resulting from neuroelectric activity in specifiable frequency bands. Methods: Simulations, phantom experiments, and in vivo experiments using an eyes‐open/eyes‐closed task in 8 healthy volunteers were performed to demonstrate its sensitivity and specificity for detecting oscillatory neuroelectric activity in the alpha‐band (8‐12 Hz). A comprehensive postprocessing procedure was designed to enhance the neuroelectric signal, while minimizing any residual hemodynamic and physiological confounds. Results: The phantom results show that this technique can detect 0.06‐nT magnetic field oscillations, while the in vivo results demonstrate that it can image task‐based modulations of neuroelectric oscillatory activity in the alpha‐band. Multiple control experiments and a comparison with conventional BOLD functional MRI suggest that the activation was likely not due to any residual hemodynamic or physiological confounds. Conclusion: These initial results provide evidence suggesting that this new technique has the potential to noninvasively and directly image neuroelectric activity in the human brain in vivo. With further development, this approach offers the promise of being able to do so with a combination of spatial and temporal specificity that is beyond what can be achieved with existing neuroimaging methods, which can advance our ability to study the functions and dysfunctions of the human brain.